+0  
 
+1
389
1
avatar+165 

How do you get this function: h(x) = −2(x − 2)^2 + 2, to turn into this function: h(x)−2x^2 + 8x − 6?

Show work please.

Absolutezero  Jun 2, 2017

Best Answer 

 #1
avatar+17745 
+1

h(x)  =  -2(x - 2)2 + 2

h(x)  =  -2(x - 2)(x - 2) + 2

h(x)  =  -2(x2 - 2x - 2x + 4) + 2                   [Use FOIL]

h(x)  =  -2(x2 - 4x + 4) + 2                          [Simplify]

h(x)  =  -2x2 + 8x - 8 + 2                             [Distribute the -2] 

h(x)  =  -2x2 + 8x - 6                                   [Simplify]

geno3141  Jun 2, 2017
 #1
avatar+17745 
+1
Best Answer

h(x)  =  -2(x - 2)2 + 2

h(x)  =  -2(x - 2)(x - 2) + 2

h(x)  =  -2(x2 - 2x - 2x + 4) + 2                   [Use FOIL]

h(x)  =  -2(x2 - 4x + 4) + 2                          [Simplify]

h(x)  =  -2x2 + 8x - 8 + 2                             [Distribute the -2] 

h(x)  =  -2x2 + 8x - 6                                   [Simplify]

geno3141  Jun 2, 2017

35 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.